Bioanalytical method validation to quantify ketorolac in human vitreous and aqueous via surrogate matrix of human plasma - Prajita Pandey; Brianna A. White; Colin Goswell; Neelanjan Bose; Sara Butterworth Connell; Nicolee Schulze; Jim Nevelos; Ana Najafi; Ramin Najafi; Ryan K. Cheu (Future Science OA)
Purpose Intracameral phenylephrine 1.0%/ketorolac 0.3% (OMIDRIA®) is used during cataract surgery to prevent intraoperative miosis and reduce postoperative pain. Although studied in beagles, no human data exist showing the duration ketorolac remains in the eye postoperatively. A clinical trial measuring ketorolac concentrations in aqueous/vitreous samples necessitated the development of a validation process for acquiring these measurements. Due to limited human aqueous/vitreous humor sample availability, a bioanalytical method was developed and validated to quantify ketorolac levels using human plasma as a surrogate matrix.Methods The developed process involves extracting ketorolac and its internal standard (ketorolac-d5) from plasma as a surrogate for aqueous and vitreous humor using a protein precipitation sample preparation technique, followed by liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis.Results The validated method can be successfully applied for quantitation of ketorolac over a concentration range of 2.5 ng/mL to 5000 ng/mL. The method met the acceptance criteria with respect to selectivity, specificity, precision, accuracy, linearity, dilution integrity, and stability.Conclusions The validated method can use plasma as a surrogate matrix for quantitation of ketorolac in aqueous and vitreous humor, thereby eliminating the need to procure human vitreous and aqueous samples for validation prior to initiation of a clinical trial.